Evaluation Analysis of Using Tracer on Medical Record Storage - Ikawati, Fita Rusdian; Rusdi, Achmad Jaelani (Budapest International Research and Critics University, 2021)
Tracer is one of the facilities in the medical record filing room that can be used as medical record storage to facilitate the detection of its existence. Several studies show that there are still missfiles in medical record files. This can make services to patients often delayed and not timely because medical records are very important for patients. The purpose of this study will be to analyze the importance of evaluating the use of tracers in order to achieve the best quality of health institutions. The research method used is qualitative research with a literature review. The secondary data used for the literature review are15 peer-reviewed journal articles published between 2019-2021 on evaluation of the use of tracers of health agencies spread throughout Indonesia. The findings indicate that there is a need for a good medical record document storage system in the form of a tracer to maximize the service quality of health agencies, both puskesmas and hospitals throughout Indonesia.